2010
DOI: 10.1002/ange.201005274
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Base Interaction between Transition‐Metal Hydrides: Dihydrogen Bonding and Dihydrogen Evolution

Abstract: H2‐Bildung: Die Reaktion des sauren Wolfram(II)‐hydrids 2 mit dem Nickel(II)‐Pinzettenkomplex 1 in THF oder Toluol führte nach Bildung einer H‐H‐Brücke zur Ni‐W‐Spezies 3 (siehe Bild). Das erste Beispiel für eine H‐H‐Brücke zwischen zwei Metallhydriden mit entgegengesetzter Polarität wurde anhand von NMR‐ und IR‐Spektroskopie, Röntgenstrukturanalyse und DFT‐Berechnungen untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The experimental evidence for such DHBs was provided by VT-NMR and VT-IR spectroscopic studies of the pincer hydrides ( tBu PCP)MH (M = Ni, Pd) and the tungsten complex CpWH(CO) 3 . 174,176 The changes observed in 1 H NMR and IR spectra were similar to those for the interactions of ( tBu PCP)-MH with alcohols 174,176,325 and of CpWH(CO) 3 with bases, 317,318 although they were significantly smaller, in accord with their very low DHB formation enthalpies: ΔH°D HB = −1.0 and −1.2 kcal•mol −1 for nickel and palladium, respectively. The computational (DFT/M06) analysis revealed interesting peculiarities of these complexes.…”
Section: Dihydrogen Bonding Between Two Hydride Complexes Mh•••hm′ An...supporting
confidence: 56%
See 1 more Smart Citation
“…The experimental evidence for such DHBs was provided by VT-NMR and VT-IR spectroscopic studies of the pincer hydrides ( tBu PCP)MH (M = Ni, Pd) and the tungsten complex CpWH(CO) 3 . 174,176 The changes observed in 1 H NMR and IR spectra were similar to those for the interactions of ( tBu PCP)-MH with alcohols 174,176,325 and of CpWH(CO) 3 with bases, 317,318 although they were significantly smaller, in accord with their very low DHB formation enthalpies: ΔH°D HB = −1.0 and −1.2 kcal•mol −1 for nickel and palladium, respectively. The computational (DFT/M06) analysis revealed interesting peculiarities of these complexes.…”
Section: Dihydrogen Bonding Between Two Hydride Complexes Mh•••hm′ An...supporting
confidence: 56%
“…The hydridic hydride ligand of ( tBu PCP)MH appeared to interact with both the "protic" hydride ligand and one of the Cp ring hydrogens of CpWH(CO) 3 (see Figure 32). The length of the H Pd •••H W bond (2.43 Å) was found to be smaller than the H These DHB complexes are stable only at low temperatures and gradually liberate H 2 above 230−250 K. 174,176 The activation enthalpy and entropy values are substantially higher for the nickel hydride than for the palladium hydride: ΔH The reaction mechanism (Scheme 24) suggested on the basis of experimental and theoretical data includes proton transfer as the rate-determining step. The approach of two metal-bound hydrogens affords a H 2 molecule bridging the two metal atoms in a μ,η 1:1 -end-on fashion.…”
Section: Dihydrogen Bonding Between Two Hydride Complexes Mh•••hm′ An...mentioning
confidence: 90%
“…Shubina and co‐workers recently reported that complex 2 evolves hydrogen gas upon reaction with a tungsten carbonyl hydride complex. An unconventional bridging dihydrogen complex intermediate was implicated, based on low temperature spectroscopy 5. In very recent work, complex 1 was proposed as an intermediate in the electrocatalytic production of hydrogen 6…”
Section: Methodsmentioning
confidence: 99%
“…An unconventional bridging dihydrogen complex intermediate was implicated, based on low temperature spectroscopy. [5] In very recent work, complex 1 was proposed as an intermediate in the electrocatalytic production of hydrogen. [6] Similarly, there are few examples of molecular Ni II -(N 2 ) complexes.…”
mentioning
confidence: 99%
“…Tungsten complex CpW(CO) 3 H bears an acidic hydride and thus is capable of protonating nickel hydrides like ( tBu PCP tBu )-NiH (Scheme 74). 226 The final product is a heterobimetallic complex featuring CpW(CO) 3 bound to nickel via the oxygen end of a CO ligand. The reaction monitored at −83 °C reveals an interesting adduct that contains a dihydrogen bond.…”
Section: Protonation By Acidsmentioning
confidence: 99%